Cultural cooperation in South Asia : the search for community : papers and proceedings of the Fifth South Asian Dialogue - Caudhurī, Jāmila (Centre for Policy Dialogue : University Press, 1999)
Chiefly covers topics on social justice and human rights, women in society, and fundamentalism and communalism.